Dampak Program Pembiayaan Mikro terhadap Peningkatan Kesejahteraan Pelaku UMKM: (Studi Kasus pada Koperasi Wanita Desa Minggirsari, Kabupaten Blitar) - Dita Ayu Primantari; Wydha Mustika Maharani; Abdul Aziz Al Kaharudin (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2025)
The main issue faced by MSME actors is limited capital, which hinders business development and their well-being. This study aims to evaluate the impact of the micro-financing program on improving the well-being of MSME actors, with a case study at the "Maju Makmur" Women’s Cooperative in Minggirsari Village. Using a qualitative approach, the study found that the provision of capital to MSME actors in the cooperative has been well-implemented and has had a positive impact, particularly in increasing income, economic activities, and the ability to meet daily needs. Supporting factors for the success of this program include government funding support, good cooperative management, clear implementation and technical guidelines, and community support. On the other hand, hindering factors include the presence of other financial institutions in the village, causing cooperative members to have savings in other places, as well as bad loans and a lack of socialization regarding the micro-financing program. Overall, the micro-financing program at the "Maju Makmur" Women's Cooperative has significantly benefited the improvement of MSME actors' well-being in Minggirsari Village.